ANALYSIS OF THE FEASIBILITY STUDY OF WASTE TO ENERGY INVESTMENT IN DKI JAKARTA : A CASE STUDY AT PT EMAS HIJAU ENERGI - Faizin, Agus
Waste management is still a problem that needs an immediate solution for DKI Jakarta. The Intermediate Treatment Facilities (ITF) is a concept of reducing and managing waste through a technology which is a renewable energy that can reduce the number of piles up from the source and reduce emissions, which in the processing process can be utilized into energy products (electricity). ITF is based on the waste to energy concept by heating the waste into a closed room called an incinerator. This project is touted as one of the largest waste processing sites in the world because it is able to process 2,000 tons/day of waste. The processing and utilization of waste in various areas is expected to be one solution to reduce the burden of waste in the Bantar Gebang Integrated Waste Processing Site (TPST). It is also as the action to following up the Presidential Decree 35/2018 concerning Acceleration of Construction of Waste Processing Installations into Electricity-Based Energy Based on Environmentally Friendly Technology and as a contributions to accelerate the collaboration of the city of Jakarta and its citizens in optimizing sustainable clean energy without relying on fossil fuels, in accordance with the 2015 Paris Agreement.